Residual foreign body in the foot causing chronic osteomyelitis mimicking a pseudotumor: A case report - Yin-Ming Huang; Shan-Wei Yang; Chun-Yu Chen; Chine-Jen Hsu; Wei-Ning Chang (Journal of International Medical Research, 2020)
Osteomyelitis from a retained foreign body should be included in the differential diagnosis of any osteolytic lesion of the foot. We report here a case of a 59-year-old man who presented with swelling over the dorsolateral aspect of the right foot. Plain x-ray showed an osteolytic lesion that mimicked a pseudotumor. Magnetic resonance imaging (MRI) showed multilocular fluid collection over the right cuboid with a hypointense lesion over the plantar fascia. The patient underwent surgery and a rubber fragment (1 cm × 0.8 cm) was removed from his foot that had been present for two years following a stabbing injury. The patient fully recovered without complication or disability.